Snakes and Sacrifices: Tentative Insights into the Pre-Christian Ethiopian Religion - Manzo, Andrea (Aethiopica, 2014)
Despite the recent efforts which were recently made in this field of study, our knowledge of the pre-Christian religion of Aksumite Northern Ethiopia remains very limited. This article presents the contribution that archaeology can make to debate on this topic. In particular, some archaeological finds from Betä Giyorgis, north of Aksum, and from Aksum itself which can be related to the cult of the snake and to the practice of human sacrifices are described. These finds, dating from the Proto-Aksumite (3rd–1st centuries B.C.) and the first part of the Aksumite (1st–4th centuries A.D.) periods, may support the reality of the cult of the snake and of the practice of human sacrifices, two elements characterizing the Ethiopian traditions related to Arwe, the mythic snake-king of Aksum. In the conclusions, these specific aspects which may have characterized the pre-Christian Ethiopian religion are put in a broader regional context, compared to what is known about similar cultic traits in the Nile valley, in the Near East, and in South Arabia. Possible links to be explored with further research covering the different traditions are suggested. Moreover, a possible evolution in the meaning of the snake in Ethiopia, from benevolent and helpful entity to dangerous monster, and, finally, to symbol of sin, is outlined.